Acetyltransferase p300 regulates atrial fibroblast senescence and age‐related atrial fibrosis through p53/Smad3 axis. Issue 1 (5th December 2022) - Gao, Xiao‐Yan; Lai, Ying‐Yu; Luo, Xue‐Shan; Peng, De‐Wei; Li, Qiao‐Qiao; Zhou, Hui‐Shan; Xue, Yu‐Mei; Guo, Hui‐Ming; Zhao, Jun‐Fei; Yang, Hui; Kuang, Su‐Juan; Wang, Zhao‐Yu; et al.
Abstract: Atrial fibrosis induced by aging is one of the main causes of atrial fibrillation (AF), but the potential molecular mechanism is not clear. Acetyltransferase p300 participates in the cellular senescence and fibrosis, which might be involved in the age‐related atrial fibrosis. Four microarray datasets generated from atrial tissue of AF patients and sinus rhythm (SR) controls were analyzed to find the possible relationship of p300 (EP300) with senescence and fibrosis. And then, biochemical assays and in vivo electrophysiological examination were performed on older AF patients, aging mice, and senescent atrial fibroblasts. The results showed that (1) the left atrial tissues of older AF patients, aging mouse, and senescence human atrial fibroblasts had more severe atrial fibrosis and higher protein expression levels of p300, p53/acetylated p53 (ac‐p53)/p21, Smad3/p‐Smads, and fibrosis‐related factors. (2) p300 inhibitor curcumin and p300 knockdown treated aging mouse and senescence human atrial fibroblasts reduced the senescence ratio of atrial fibroblasts, ameliorated the atrial fibrosis, and decreased the AF inducibility. In contrast, over‐expression of p300 can lead to the senescence of atrial fibroblasts and atrial fibrosis. (3) p53 knockdown decreased the expression of aging and fibrosis‐related proteins. (4) Co‐immunoprecipitation and immunofluorescence showed that p53 forms a complex with smad3 and directly regulates the expression of smad3 in atrial fibroblasts. Our findings suggest that the mechanism of atrial fibrosis induced by aging is, at least, partially dependent on the regulation of p300, which provides new sights into the AF treatment, especially for the elderly. Abstract : Atrial tissue p300 levels increase in aged mice along with the atrial fibrosis and high incidence of atrial fibrillation. p300 participates in the age‐related fibrosis through regulating p53/Smad3 pathway. Pharmacological inhibition or gene knockdown of this p300‐dependent pathway attenuates the onset and progression of age‐induced atrial fibrillation.